2018
DOI: 10.3389/fncom.2017.00115
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography Amplitude Modulation Analysis for Automated Affective Tagging of Music Video Clips

Abstract: The quantity of music content is rapidly increasing and automated affective tagging of music video clips can enable the development of intelligent retrieval, music recommendation, automatic playlist generators, and music browsing interfaces tuned to the users' current desires, preferences, or affective states. To achieve this goal, the field of affective computing has emerged, in particular the development of so-called affective brain-computer interfaces, which measure the user's affective state directly from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 66 publications
2
33
0
Order By: Relevance
“…Standard filtering may be an aspect of the preprocessing phase, with EEG signals seeing the introduction of further software filters-band pass and notch filters for example-to carry out this process. As a means of restricting EEG signal frequencies in accordance with [76], a higher cutoff frequency around 64 Hz and a low cutoff of 0.5 Hz (3 dB) was adopted for the band pass filter. A 50 Hz cutoff frequency was adopted for the notch filter; eliminating A/C electricity line interference is the typical reason for doing so [38].…”
Section: Preprocessing Stagementioning
confidence: 99%
“…Standard filtering may be an aspect of the preprocessing phase, with EEG signals seeing the introduction of further software filters-band pass and notch filters for example-to carry out this process. As a means of restricting EEG signal frequencies in accordance with [76], a higher cutoff frequency around 64 Hz and a low cutoff of 0.5 Hz (3 dB) was adopted for the band pass filter. A 50 Hz cutoff frequency was adopted for the notch filter; eliminating A/C electricity line interference is the typical reason for doing so [38].…”
Section: Preprocessing Stagementioning
confidence: 99%
“…Moreover, as the DEAP database relies on 9-point scale ratings, it has typically been the case where the midpoint is considered as a threshold, where ratings greater than the threshold are considered “high,” and those below are considered “low”. As was recently emphasized in [4], however, subjects have their own internal biases, thus leading to varying scales for grading and, consequently, different thresholds per participant. For example, as reported in [4], by using a midpoint threshold value of 5, a 60/40 ratio of high/low levels was obtained across all participants.…”
Section: Methodsmentioning
confidence: 99%
“…For example, affective computing can enable applications in which the machine can learn user preferences based on their reactions to different settings or even become a more effective tutor by assessing the student's emotional/stress states [3]. Automated recommender and tagging systems, in turn, can make use of affect information to better understand user preferences, thus improving system usability [4]. Measuring affective state and engagement levels can also be used by a machine to infer the user's perceived quality of experience [59], thus providing the machine with an objective criterion for online optimization.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the global field synchronization—a measure calculated using EEG signals acquired from the entire brain—was reported to be effective for estimating users’ emotional valence [ 24 ]. Additionally, Clerico et al reported that the use of connectivity features between multiple interhemispheric electrode pairs could enhance the overall accuracy of emotion classification [ 25 ]. However, a cumbersome preparation process is generally involved for appropriately wearing the devices, as the electrodes must remain in tight contact with the scalp surface in the hair-bearing area [ 26 ].…”
Section: Introductionmentioning
confidence: 99%